1994
DOI: 10.1063/1.466796
|View full text |Cite
|
Sign up to set email alerts
|

Differential cross sections for fine structure transitions in O(3P2)+Ar collisions

Abstract: We present experimental and theoretical differential cross sections for the fine structure changing process Ar + O(3P2)→Ar + O(3Pjmj) with (j,mj)=(1,1), (1,0), and (0,0). The measured cross sections refer to a collision energy of 3.2 kcal/mol, and were obtained from Doppler line shapes associated with (2+1) resonance-enhanced multiphoton ionization of O(3Pjmj) after scattering in a crossed-beam apparatus. The theoretical results are based on 3Σ− and 3Π potential curves obtained from high quality ab initio calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Inelastic transitions in the RgϩX( 3 P) collisions have been studied in several works, see, e.g., Refs. 29,30,[44][45][46][47]55. It is well known that the electrostatic interaction which preserves the bodyfixed projection ⍀ of j ͑and simultaneously of the total angular momentum J͒ couples the jϭ0, 2 and jϭ1, 2 pairs of levels.…”
Section: Intramultiplet Transitions In Rg¿s Collisionsmentioning
confidence: 99%
“…Inelastic transitions in the RgϩX( 3 P) collisions have been studied in several works, see, e.g., Refs. 29,30,[44][45][46][47]55. It is well known that the electrostatic interaction which preserves the bodyfixed projection ⍀ of j ͑and simultaneously of the total angular momentum J͒ couples the jϭ0, 2 and jϭ1, 2 pairs of levels.…”
Section: Intramultiplet Transitions In Rg¿s Collisionsmentioning
confidence: 99%
“…Using a similar setup, previous studies demonstrated that most of O atoms (∼98%) were supersonically cooled to the lowest fine-structure state O( 3 P 2 ). 29,30 Because of the high barrier to reaction, the CHD 3 beam was also seeded (∼20%) in H 2 for acceleration. To investigate the initial translational energy dependence of the reactivity, the intersection angle of the two molecular beams was varied, thereby changing the relative collision energy in the center-of-mass frame.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…They have also been observed in reactive collisions of open-shell atoms with closed-shell molecules [8][9][10][11] and alignment-specific behavior in the reactive cross sections has sometimes been noted. In theoretical studies of inelastic atom-atom collisions, Coriolis effects have been addressed occasionally [12][13][14][15] but there have been essentially no theoretical studies of Coriolis effects in reactive collisions. In this paper we would like to address this issue along with other aspects of nonadiabatic reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%